2012
DOI: 10.1667/rr2913.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Low- and High-Dose-Irradiated Human Peripheral Blood Lymphocytes: Possible Applications for Biodosimetry

Abstract: To overcome the limitations of existing biodosimetry methods, we examined dose- and time-dependent gene expression changes in human peripheral blood lymphocytes after exposure to low-, medium- and high-dose ionizing radiation and searched for genes suitable for predicting radiation doses in the low-dose range. Additionally, the experiments are intended to provide new insights into the biological effects of exposures to low-, medium- and high-dose radiation. Gene expression analysis using whole human genome DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 31 publications
2
65
1
Order By: Relevance
“…It has been reported many times that the quantification of gene expression in response to radiation exposure by microarray technology is robust and reliable (Paul & Amundson 2008;Boldt et al 2012;Knops et al 2012), and the obtained gene signatures derived in ex situ irradiated blood are shown to be predictive for the radiation dose in vitro as well as in vivo (Paul et al 2011). The gene signature developed by Boldt et al (2012) was reported to be robust in terms of dose prediction.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It has been reported many times that the quantification of gene expression in response to radiation exposure by microarray technology is robust and reliable (Paul & Amundson 2008;Boldt et al 2012;Knops et al 2012), and the obtained gene signatures derived in ex situ irradiated blood are shown to be predictive for the radiation dose in vitro as well as in vivo (Paul et al 2011). The gene signature developed by Boldt et al (2012) was reported to be robust in terms of dose prediction.…”
Section: Discussionmentioning
confidence: 97%
“…Detailed analysis protocols for Labs 1, 2 and 3 are described in Abend et al (2016). DNA microarrays (44 k whole human genome, G4112F, Agilent) were performed according to the manufacturer's protocols and as described in Knops et al (2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared our findings with a previously used gene in GE biodosimetry, FDXR (Boldt et al 2012;Kabacik et al 2011;Knops et al 2012;Manning and Rothkamm;Paul and Amundson, 2008), which is regulated by p53 family and with our previous in vitro study (Khodamoradi et al In Press). In our pervious study, we found the dose response curve of the FDXR and RAD51 genes in response to different doses and 6 and 18 MV beam energies in human PBLs.…”
Section: Discussionmentioning
confidence: 99%